Kontribusi Lingkungan Organisasi Terhadap Peningkatan Kualitas Aplikasi Keuangan Survey Pada Perbankan BUMN - Lilis Puspitawati; Popy Gurning; Nanang Suryana (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
The quality of the financial application is highly dependent on the organizational environment in which the information system is used. This concept is in line with the facts found in the field that until now the quality of accounting information system applications used by various companies is still relatively low because they often experience errors and are not well integrated which have an impact on the low quality of accounting information. This study aims to determine whether organizational environmental factors in this case represented by organizational structure and culture still have an influence on the quality of accounting information systems. This research uses the descriptive verification method. The sample size in this study was 30 employees of operational units who use accounting information system applications at state-owned banks with branch offices in Bandung, this study uses primary data collected by distributing questionnaires. Statistical testing used is PLS-SEM and hypothesis testing using PLS 3.0 smart software. The results of this study indicate that there is consistency with the results of previous studies that the increasing implementation of organizational culture has an impact on increasing the quality of accounting information systems, and the more effective organizational structure has an impact on the quality of accounting information systems.